Comparison of two point-of-care lung ultrasound techniques and their associated outcomes for bronchiolitis in the pediatric emergency department - Smith, Jaron A.; Cooper, Michael C.; Yen, Kenneth; Reisch, Joan; Stone, Bethsabee S. (The Ultrasound Journal, 2025)
Background: Acute bronchiolitis (AB) is the most common lower respiratory tract infection in infants. Clinician diagnosis and management vary due to limited objective assessment tools. Point-of-care lung ultrasound (LUS) offers a promising diagnostic and prognostic tool in the emergency department (ED), however, the time to perform LUS is of concern in the emergency setting.Methods: Infants ≤ 12 months diagnosed with AB in the emergency department were enrolled. Two LUS techniques were performed sequentially: a 12-segment “lawnmower” approach and a posterior paravertebral “waterfall” technique. LUS were scored (0–36 for lawnmower; 0–6 for waterfall). Respiratory support (RS) was categorized into three levels: no RS (room air), low RS (wall O2 or heated high flow nasal cannula < 1L/kg), and high RS (heated high flow nasal cannula ≥ 1L/kg or positive pressure). Clinical data, including RS at 12 and 24 h, maximum RS, disposition, and length of stay, were extracted via chart review and compared to mean LUS scores for each technique. Calculated areas under the curve (AUC) were compared using the Youden Index (J).Results: 82 infants were enrolled. The mean waterfall scanning time was 1.65 min (SD 0.55) compared to the lawnmower’s 7.65 min (SD 1.45). The difference between mean LUS scores for the waterfall technique was statistically significant for all disposition comparisons and nearly all RS comparisons. While the lawnmower AUC was greater than the waterfall AUC for all RS and disposition comparisons, the Youden Index (J) was statistically significantly different for only two of the eight comparisons.Conclusion: The posterior-only LUS technique is faster than the lawnmower technique, provides comparable information for disposition, and has a stronger association with LOS, but is less associated with RS. The waterfall technique may be a suitable alternative to more time-intensive, thorough techniques.